Influence of musical-rhythmic means education on the level of development of artistic athletes 6-8 years in rhythmic gymnastics - Mullagildina, A.; Bilenka, I.; Kobelieva, N. (Slobozhanskyi herald of science and sport, 2018)
Purpose: investigate the impact of musical rhythmic education on the development of artistic abilities of gymnasts 6-8 years.